Calanus glacialis and C. finmarchicus in a warming Arctic Implications of increasing temperature at the individual and population level - Grote, Ulrike (UiT The Arctic University of Norway, 2017)
The papers I, III and IV of this thesis are not available in Munin. Paper I: Grote U., Pasternak A., Arashkevich E., Halvorsen E., Nikishina A.: "Thermal response of ingestion and egestion rates in the Arctic copepod Calanus glacialis and possible metabolic consequences in a warming ocean". Available in Polar Biology 2015, 38:1025-1033. Paper III: Pasternak, A.F., Arashkevich, E.G., Grote, U., Nikishina, A.B., Solovyev, K.A.: Different effects of increased water temperature on egg production of Calanus finmarchicus and C. glacialis. Available in Oceanology 2013, 53(5):547-553. Paper IV: Grote U., Eisenhauer L.: "Modelling population level responses of Calanus glacialis and C. finmarchicus under different climate warming regimes in the Barents Sea area". (Manuscript). Climate change is particularly pronounced in the Arctic and water temperatures are predicted to increase substantially. This has important implications for Arctic marine organism, especially ectotherms, such as copepods. The calanoid copepods Calanus glacialis and C. finmarchicus are key species of different pelagic food webs at high latitudes and changes in temperature will likely affect them differently, further affecting higher trophic level organisms feeding on Calanus spp. One objective of this thesis was therefore to investigate physiological processes affecting growth and reproduction, such as feeding, egestion, respiration, and egg production rates of especially C. glacialis in response to temperature (0 10 °C) and to discuss the potential metabolic balance. The other objective of this thesis was to investigate the effect of increasing temperature on C. glacialis and C. finmarchicus populations using the SINMOD model. C. glacialis ingestion and egestion rates increased linearly with temperature in one experiment, while ingestion and respiration rates reached a thermal optimum at 2.5 °C and 6 °C, respectively, in another experiment, indicating plasticity in feeding responses, likely due to local adaptation. Comparing the Q10 values of ...